(untitled) (Bodhi Path, 2023)
The Pali literature is derived from the moral teachings of the great ascetic Gautama Buddha and is considered an invaluable treasure in India and other regions. Other Buddhist literature is also unique and quite extensive in terms of size. Pitaka, Abhidhamma, Jatakas, poetry, grammar, and so on are the different sections of the diverse Pali literature. Pitaka - Vinaya Pitaka, Sutta Pitaka, Abhidhamma Pitaka. Abhidhamma- Nettippakarana, Petakopadesa, Milindapannha. Jatakas- Samantapasadika, Sumangalavilasin, Papancasudani, Saratthappakasini, Manorathapurani, Paramatthajotika etc. Poetry-(Jinalankara, Jinavatthu, Pugalmadhu, Tettakatthagatha, Saddhammopayana, Panchagatidipa, Lokaniti etc) and Vyakarana. The Pali literature describes the moral teachings of Buddha and his followers, as well as the religious and philosophical beliefs of ancient India, including details of various forms of art, political situations, economic conditions, social customs, and the status of people in society.